Маркетинг-стратегии за настап на македонските вина на пазарот во Европската Унија - Димовска, Ана (Економски факултет, УКИМ, Скопје, 2017)
The Republic of Macedonia has all the necessary prerequisites for production of high quality wines and has great export potential, but Macedonian wines are almost unknown on the world wine market. Another problem is that most of the quantities exported are in the form of bulk wine, although in recent years the ratio between bulk and bottled wine started to change positively in terms of bottled wine. This paper gives a detailed overview of the strengths and weaknesses of the Macedonian wine industry, as well as concrete strategies how to use them in the export of Macedonian wines on the international markets. In the overview of the domestic wine market, results of an empirical research on the segmentation of Macedonian wine consumers are presented. The results of the research can help wineries in the selection of target groups to direct their efforts on the domestic market. The wine market in the EU has been elaborated in detail as the most important export destination for Macedonian wines. Given the specificities of the wine market of individual EU member states, this paper helps selecting the countries in which the largest export of wine can be achieved. For the targeted markets, measures and activities are proposed for each element of the marketing mix. Crucially for achieving any success on international markets and increasing wine exports is building the image and promotion of Macedonian wines. This is possible only with the strong support of the state and the competent institutions in the promotion of the Macedonian wine industry. Without establishing and developing a strong umbrella wine brand, Macedonian wines would be lost in intense competition on the world wine market.
Marketing strategies for Macedonian wines in the EU
Докторска дисертација одбранета во 2017 година на Економскиот факултет во Скопје, под менторство на проф. д–р Снежана Ристевска Јовановска.
Keywords: Macedonia, Macedonian wines, European Union, strategies, promotion, image, umbrella brand